Knockdown of Mct1 in the arcuate nucleus increases food-anticipatory activity in mice - Martini, Tomaz; Albrecht, Urs (Frontiers in Physiology, 2025)
Animals rely on internal time-keeping mechanisms to anticipate regular events such as feeding, allowing preemptive gene expression which enables timely physiological responses. A manifestation of anticipatory mechanisms is also a rise in body temperature and activity before a predictable mealtime. The activity, which resembles food seeking, depends on the communication between peripheral organs and the brain. The liver plays a central role by producing metabolic signals, including beta-hydroxybutyrate, which is released into the blood in anticipation of feeding. This release is controlled by the transporter MCT1, and its hepatic ablation in mice impairs food-anticipatory activity (FAA). However, in parallel, loss of MCT1 in the arcuate nucleus, a brain nucleus that orchestrates feeding behaviour, was implicated in increased food intake, creating a paradox. Here, we demonstrate that MCT1’s role in feeding behavior is tissue dependent, and that while hepatic and systemic disruption of Mct1 impair FAA, arcuate nucleus Mct1 knockdown increases FAA. This underscores the complexity of small molecule signalling in metabolism, of which MCT1 is merely a transporter, and whose actions are ligand, and hence context and tissue dependent.